Risk factors for intraoperative in-stent thrombosis during stent-assisted coiling of paraclinoid aneurysms - Zeng, Chun; Wang, Jing (Frontiers in Neurology, 2024)
Objectives To identify independent risk factors for intraoperative in-stent thrombosis (IST) in paraclinoid aneurysms (PAs). Methods 172 PA patents undergoing stent-assisted coiling (SAC) were divided into an IST group (n = 12) and a non-IST group (n = 160). Clinical characteristics, aneurysm morphologies, and laboratory parameters were measured. We performed independent t tests (for normally distributed data) or non-parametric tests (for non-normally distributed data) to compare continuous parameters. Multivariate logistic regression analysis with a stepwise forward method was conducted to determine independent risk factors. Receiver operating characteristic curves were generated, and the Delong test was employed for comparisons. Results Independent risk factors for IST included size ratio (SR) (p < 0.001, odds ratio [OR] = 3.909, confidence interval [CI] = 1.925–7.939), adenosine diphosphate (ADP) inhibition (p = 0.028, OR = 0.967, CI = 0.938–0.996), and reaction time (R) (p = 0.006, OR = 0.326, CI = 0.147–0.725). The combined factors (SR, ADP inhibition, and R) exhibited area under the curves of 0.870, 0.720, 0.716, and 0.697, with cutoff values of 2.46, 69.90%, and 4.65, respectively. Conclusion The SR, ADP inhibition, and R values were independent risk factors for the IST in the PAs undergoing SAC. For PAs with a large SR, surgeons could prepare for long-term dual antiplatelet therapy before SAC.